Latent Transformatin of Generations Existence in Smart Society - Sharonova, S.A.; Avdeeva, E.V. (KnE Social Sciences, 2021)
The rapid development of information technologies in the formation of online or digital environments has a significant impact on the transformation of society contributing to the development of Smart society. This is largely due to the formation of a Smart environment based on the introduction of new technologies. In changing the patterns of social life, these new technologies require and stimulate the transformation of social norms and values. For example, simplified communication between people, expressed in the transfer of instant messages through mobile applications (messengers) gains popularity. Such messages replace verbal communication through mobile devices. The use of modern digital technologies contributes to developing new characteristics of activities, for example, multitasking, which is expressed in the ability to conduct several conversations and perform several actions in parallel. The aim of this study is to find the main trends and differences, and predict the behavior patterns of different age groups in the process of forming a Digital society. Changes can happen swiftly or slowly, in part determined by the speed of release of new information products. There is a latent transformation of generations’ existence in modern society from natural to imposed forced skills against the backdrop of these technological transformations. This research has identified the differences in the perception and attitude of different age groups to this transformation. Keywords: Smart society, Digital society, smart environment, digital media